How brains beware: neural mechanisms of emotional attention - Vuilleumier, Patrik (Trends in cognitive sciences, 2005)
Emotional processes not only serve to record the value of sensory events, but also to elicit adaptive responses and modify perception. Recent research using functional brain imaging in human subjects has begun to reveal neural substrates by which sensory processing and attention can be modulated by the affective significance of stimuli. The amygdala plays a crucial role in providing both direct and indirect top-down signals on sensory pathways, which can influence the representation of emotional events, especially when related to threat. These modulatory effects implement specialized mechanisms of ‘emotional attention’ that might supplement but also compete with other sources of top-down control on perception. This work should help to elucidate the neural processes and temporal dynamics governing the integration of cognitive and affective influences in attention and behaviour.